2022
DOI: 10.47102/annals-acadmedsg.2021297
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of delirium in post-anaesthesia care unit

Abstract: Introduction: Post-anaesthesia care unit (PACU) delirium is a potentially preventable condition that results in a significant long-term effect. In a multicentre prospective cohort study, we investigate the incidence and risk factors of postoperative delirium in elderly patients undergoing major non-cardiac surgery. Methods: Patients were consented and recruited from 4 major hospitals in Singapore. Research ethics approval was obtained. Patients older than 65 years undergoing non-cardiac surgery >2 hours wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In the clinical setting, it has been observed that intraoperative hyperglycemia is an independent risk factor for delirium in elderly patients. Ke et al conducted a study and found that higher randomized blood glucose levels (> 9.5 mmol/L) were positively associated with delirium in the post-anesthesia care unit, as determined by multivariate analysis [50]. Moreover, previous research has shown a signi cant association between the duration of intraoperative hyperglycemia (blood glucose > 8.3 mmol/L) and postoperative delirium [14].…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical setting, it has been observed that intraoperative hyperglycemia is an independent risk factor for delirium in elderly patients. Ke et al conducted a study and found that higher randomized blood glucose levels (> 9.5 mmol/L) were positively associated with delirium in the post-anesthesia care unit, as determined by multivariate analysis [50]. Moreover, previous research has shown a signi cant association between the duration of intraoperative hyperglycemia (blood glucose > 8.3 mmol/L) and postoperative delirium [14].…”
Section: Discussionmentioning
confidence: 99%
“… 37 Recent studies have shown that older patients have a higher incidence of delirium in the PACU after surgery. 38 Therefore, early assessment, appropriate intervention, and prevention are necessary to reduce medical costs and improve the quality of life after surgery. To achieve this goal, this trial will plan to evaluate patients for delirium using the Nu-DESC tool in the postoperative PACU and on days 1 and 2 after surgery.…”
Section: Methodsmentioning
confidence: 99%
“…The Nursing Delirium Screening Scale (Nu-DESC) tool is a highly sensitive and specific instrument for screening postoperative delirium, including symptoms such as disorientation, behavioural abnormalities, communication disorders, hallucinations or delusions, psychomotor retardation, and other related symptoms 37. Recent studies have shown that older patients have a higher incidence of delirium in the PACU after surgery 38. Therefore, early assessment, appropriate intervention, and prevention are necessary to reduce medical costs and improve the quality of life after surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical research suggests a significant link between anaesthesia and delirium 11,12 . However, due to confounding factors such as age, anaemia, medication, and others, the causal relationship between anaesthesia and delirium remains unclear 13 . Moreover, limited studies have explored the impacts of different anaesthetic methods on delirium risk.…”
Section: Introductionmentioning
confidence: 99%